Immune checkpoint inhibitors combined with tyrosine kinase inhibitors or immunotherapy for treatment-naïve metastatic clear-cell renal cell carcinoma—A network meta-analysis. Focus on cabozantinib combined with nivolumab - Niewada, Maciej; Macioch, Tomasz; Konarska, Magdalena; Mela, Aneta; Goszczyński, Adam; Przekopińska, Bogusława; Rajkiewicz, Karolina; Wysocki, Piotr; Krzakowski, Maciej (Frontiers in Pharmacology, 2023)
Introduction: The combination of immunotherapy and targeted therapy is currently marking a new era in the treatment of renal cancer. The latest clinical guidelines recommend the use of drug combinations for the first-line treatment of advanced renal cancer. The aim of this review is to compare the efficacy of combined cabozantinib + nivolumab therapy with other immune checkpoint inhibitors combined with tyrosine kinase inhibitors or monoclonal antibodies blocking the CTLA-4 (cytotoxic T cell antigen 4) in the first-line treatment of metastatic clear-cell renal cell carcinoma (RCC). Methodology: A systematic literature search was carried out in the PubMed and EMBASE databases. Randomized controlled trials (RCTs) on therapies recommended by the latest EAU and ESMO guidelines for treatment-naïve metastatic RCC (i.e., lenvatinib + pembrolizumab, axitinib + pembrolizumab and nivolumab + ipilimumab) were searched. A network meta-analysis (NMA) was performed for data synthesis. The methodology of included RCTs was assessed using the Cochrane RoB two tool. The data were analyzed in the overall population as well as in risk subgroups defined according to the International Metastatic Database Consortium (IMDC) i.e., patients with a favorable and intermediate or poor prognoses. The most recent cut-off dates from included studies were analyzed. Results: Four RCTs (CheckMate 9 ER, KEYNOTE-426, CLEAR and CheckMate 214) were included in the review. No studies directly comparing cabozantinib + nivolumab with any of the drug combinations included in this review were available. NMA showed that cabozantinib + nivolumab was superior compared to axitinib + pembrolizumab and nivolumab + ipilimumab in all analyzed comparisons (overall population and IMDC risk subgroups), both in terms of overall survival and progression-free survival (PFS). The advantage of cabozantinib + nivolumab was statistically significant only for PFS when compared to nivolumab + ipilimumab in the overall population. The results for the comparison of cabozantinib + nivolumab with lenvatinib + pembrolizumab showed numerical superiority of lenvatinib + pembrolizumab combination in terms of overall survival, but none of the results were statistically significant. The advantage of lenvatinib + pembrolizumab over cabozantinib + nivolumab in terms of PFS was statistically significant in the overall and favorable prognosis population. Conclusion: Inclusion of the most recent cut-off data from CheckMate 9 ER did not affect the role of the cabozantinib + nivolumab combination for treatment-naïve metastatic RCC. Cabozantinib + nivolumab is an effective therapeutic option for the first-line treatment of advanced renal cancer that is recommended both in the latest European and American guidelines for all IMDC risk groups.